We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
122
2
avatar+232 

7x +10 + 2x + 5= 6x-6

 Jan 28, 2019

Best Answer 

 #1
avatar+18274 
+1

7x + 2x + 10 + 5 = 6x-6    Collect 'like' terms

9x + 15 = 6x-6                   Subtract 6x from bvoth sides of the equation

3x + 15 = -6                      Subtract 15 from both sides

3x = -21                          Divide both sides by three

x = -7

 Jan 28, 2019
 #1
avatar+18274 
+1
Best Answer

7x + 2x + 10 + 5 = 6x-6    Collect 'like' terms

9x + 15 = 6x-6                   Subtract 6x from bvoth sides of the equation

3x + 15 = -6                      Subtract 15 from both sides

3x = -21                          Divide both sides by three

x = -7

ElectricPavlov Jan 28, 2019
 #2
avatar+232 
+1

Thanks

 Jan 28, 2019

11 Online Users

avatar